A pharmacovigilance study of the association between proton pump inhibitors and tumor adverse events based on the FDA adverse event reporting system database - Zhang, Ya-Jun; Duan, Dan-Dan; Tian, Qian-Yu; Wang, Cai-E.; Wei, Shu-Xun (Frontiers in Pharmacology, 2024)
BackgroundProton pump inhibitors (PPIs) are effective treatments for acid-related disorders but may pose tumor risks with long-term use. Current research on PPI-associated tumor adverse events (TAEs) is limited and inconclusive. This study aims to comprehensively analyze the relationship between PPIs and TAEs.MethodsWe analyzed PPI adverse reaction reports from the FDA Adverse Event Reporting System (FAERS) database spanning from 2004 to 2024, focusing on five commonly used PPIs: esomeprazole, pantoprazole, lansoprazole, omeprazole, and rabeprazole. We conducted a disproportionality analysis utilizing the Reporting Odds Ratio (ROR) to identify potential TAEs associated with PPIs. We conducted univariate logistic regression analysis to explore the influencing factors.ResultsA total of 3,133 TAEs were identified, representing 2.36% of all PPI-related adverse events (AEs). The most common TAEs were gastric cancer (19.05%) and malignant neoplasm (7.23%). Disproportionality analysis revealed ten significant TAEs associated with PPIs, including gastric adenocarcinoma and renal cell carcinoma. The median age of those reporting TAEs was 59 (interquartile range [IQR]: 51–70), and 29.70% of them resulted in a fatality. TAEs associated with PPIs were less likely to occur in elderly patients (65–75: OR = 0.91 [0.87–0.95], p < 0.001; >75: OR = 0.93 [0.89–0.98], p < 0.01).ConclusionTAEs constitute a small but significant fraction of PPI-related AEs. This study highlights the need for cautious long-term use of PPIs and further research to understand the underlying mechanisms and risk factors. Clinicians should be aware of the potential tumor risks associated with prolonged PPI treatment.